2016
DOI: 10.1063/1.4962544
|View full text |Cite
|
Sign up to set email alerts
|

Threading dislocation movement in AlGaN/GaN-on-Si high electron mobility transistors under high temperature reverse bias stressing

Abstract: Dislocations are known to be associated with both physical and electrical degradation mechanisms of AlGaN/GaN-on-Si high electron mobility transistors (HEMTs). We have observed threading dislocation movement toward the gate-edges in AlGaN/GaN-on-Si HEMT under high reverse bias stressing. Stressed devices have higher threading dislocation densities (i.e. ∼5 × 109/cm2) at the gate-edges, as compared to unstressed devices (i.e. ∼2.5 × 109/cm2). Dislocation movement correlates well with high tensile stress (∼1.6 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…However, later studies showed that this is not necessarily the case. Gate-edge degradation is not always accompanied by an increase of the gate-leakage current [5][6][7][8][9] and an increase of the gate-leakage current is not always accompanied by gate-edge degradation [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, later studies showed that this is not necessarily the case. Gate-edge degradation is not always accompanied by an increase of the gate-leakage current [5][6][7][8][9] and an increase of the gate-leakage current is not always accompanied by gate-edge degradation [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…With careful device and contact mask design, we propose that ECCI could even be used to track dislocation evolution in operando. This is a fascinating opportunity to explore the failure mechanisms of semiconductor devices such as GaAs/Si quantum dot lasers [37,38] and GaN [39] and SiC [40] power devices where carrier recombination or electric field-induced dislocation motion is suspected or has been observed postdegradation.…”
mentioning
confidence: 99%
“…This phenomenon correlates well with the formation of physical defects such as pits [75], cracks [13] and grooves [14] via electro-chemical oxidation process [16]. The formation of these defects is dependent on various factors such as threading dislocation [75,76], applied bias [14], temperature [77] and stressing duration [78].…”
Section: Hypothesis/problem Statementmentioning
confidence: 78%
“…For OFF-state reliability, it was found that the physical defect formation depends on various factors such as applied voltage [81], threading dislocation [75,76], environment [15], and stressing duration [78]. Several mechanisms have been proposed to explain the OFF-state degradation such as inverse piezoelectric [13], electro-chemical oxidation [16] and percolation path-induced degradation [17].…”
Section: Thesis In Context To Knowledge Gapsmentioning
confidence: 99%
See 1 more Smart Citation